Implementation of finite control set-predictive torque control based on the dSpace DS1104 controller - Rozana Alik; Nik Rumzi Nik Idris; Norjulia Mohamad Nordin; Tole Sutikno (Institute of Advanced Engineering and Science, 2026)
Finite control set-predictive torque control (FCS-PTC) has emerged as a popular control method for induction motors (IMs) over the past decade. This paper provides a detailed hardware implementation of FCS-PTC with a constant weighting factor (WF) on 186 W of IM. The FCS-PTC is implemented using the DS1104 controller board programmed using C code. A comprehensive analysis of flux, torque, and the total harmonic distortion (THD) of the stator current is conducted and presented to establish a relationship between the WF and drive performance. The experimental results indicate that a higher WF results in improved performance in flux and THD current, but a poorer torque response. Conversely, a lower WF improves torque performance but sacrifices the flux and THD current. The analysis outcome will hopefully provide some guidelines for developing the WF selection techniques.